Radiation Exposure to Nuclear Medicine Technologists During Different Diagnostic Techniques - Areeb Fatima; Taqmeem Hussain; Sumera Perveen; Arfa Mubashir; Humera Noreen (Journal of Basic & Applied Sciences, 2013)
Nuclear Medicine is being widely used, now a days, for different diagnostic purposes. The present study was planned to find out the radiation exposure to nuclear medicine technologists from radioactive patients who have gone through different diagnostic techniques. This study was carried out at Punjab Institute of Nuclear Medicine (PINUM), Faisalabad (Pakistan). In order to carry out this activity, data was collected from the nuclear medicine diagnostic techniques i.e., heart scans (Rest and Stress MIBI), bone scans, renal scans, liver scans, thyroid scans and Thallium heart scans. The radiation exposure was recorded using pen dosimeter (Arrow-Tech W138) having range 0-200mR. Heart scan (Stress MIBI) was taken as standard as it showed maximum exposure (0.584 mR) and equivalent dose corresponding to this exposure (5.85μSv) amongst all scans.